Rainfall interception in two forest species: Vochysia guatemalensis Donn. Sm. y Vochysia ferruginea Mart. - Carvajal-Vanegas, Dorian (2012)
The rainfall interception in plantations of V. ferruginea Mart. and V. guatemalensis Donn. Sm. was studied at La Selva biological station (OTS), Heredia, Costa Rica. Daily measurements of gross rainfall, throughfall and stemflow were taken from August to November 2004. Statistical tests were used to assess if the number of used rain gauges was the correct for acceptable estimates. The percentage of throughfall for V. ferruginea was 87,65% of gross rainfall, in V. guatemalensis was 92,1%. The percentages of stemflow were 2,98% y 3,39% of the gross rainfall respectively for the same species. Total interception losses in V. ferruginea were of 9,37% of the gross precipitation, in V. guatemalensis were of 4,49%.